Association between Clot Waveform Analysis Parameters and the Severity of Liver Cirrhosis - Thanapirom, Kessarin; Suksawatamnuay, Sirinporn; Thaimai, Panarat; Ananchuensook, Prooksa; Kijrattanakul, Pitiphong; Angchaisuksiri, Pantep; Tangkijvanich, Pisit; Treeprasertsuk, Sombat; Komolmit, Piyawat (Thrombosis and Haemostasis, 2025)
Clot waveform analysis (CWA) provides a global assessment of hemostasis and may be useful for patients with cirrhosis with complex hemostatic abnormalities. This study aimed to assess the association between prothrombin time (PT-) and activated partial thromboplastin time (aPTT-) based CWA parameters and cirrhosis severity and prospectively evaluate the role of CWA in predicting mortality and acute decompensation (AD) over 1 year.This prospective study included adult patients with cirrhosis between June 2021 and December 2023 at Chulalongkorn University Hospital. The PT- and aPTT-based CWA parameters were obtained using an automated coagulation analyzer.A total of 560 patients with cirrhosis were included; 165 (29.5%) and 47 (11.5%) had Child–Turcotte–Pugh (CTP) B and C cirrhosis, respectively. The PT- and aPTT-based CWA parameters, including maximum velocity (min1), maximum acceleration (min2), and maximum deceleration (max2), were significantly lower (p ≤ 0.05) in patients with decompensated cirrhosis than in those with compensated cirrhosis. Additionally, CWA values were significantly higher in patients with higher CTP and Model for End-Stage Liver Disease (MELD) scores. Multivariable analysis revealed that liver stiffness (LS) and max2 of PT-based CWA assay were independently associated with CTP B/C. In addition, min2 and max2 of PT-based CWA assay were independently associated with 1-year mortality. No significant differences in CWA parameters were observed between patients with and without portal vein thrombosis. CWA parameters were not related to AD during the 1-year follow-up.A hypocoagulable profile based on CWA parameters is associated with advanced-stage cirrhosis. CWA may be a useful objective marker for assessing cirrhosis severity and predicting 1-year mortality.
Keywords: clot wave analysis; cirrhosis; severity of liver cirrhosis; portal vein thrombosis; clinical outcomes